Efektivitas Konseling Behavioral dengan Teknik Shaping untuk Meningkatkan Self Afiliasi - Teaningsih, Ni Ketut Hefi; Suranata, Kadek; Suarni, Ni Ketut (Jurnal Jurusan Bimbingan Konseling Undiksha, 2019)
The purpose of this study was to determine the effectiveness of behavioral counseling with shaping techniques to improve self affiliation 1st grade SMA N 4 Singaraja students. This experimental study used the Pretest Postest Control Group Design. The study population was students of class 1st grade SMA Negeri 4 Singaraja, Buleleng, Bali, which numbered 349. The study sample consisted of 58 students. Through random sampling techniques, 22 students were placed in the experimental group who received a treatment model of behavioral counseling with shaping techniques and 36 students were the control group. The data in this study were analyzed by inferential t-test statistics using JASP Version 0.7.5.5 software and continued with d’Cohen to calculate the level of effectiveness. The results showed that there was a difference in the self-affiliation of the experimental group students after taking the treatment with the control group self-affiliation to get t = 17.28 with p <0.001 then p <0.05. Effect Size (ES) testing through Dohen also shows the high level of effectiveness of the behavioral counseling model (ES = 4.7). These results prove that behavioral counseling with shaping techniques is effective to improve the self-affiliation 1st grade students of SMA N 4 Singaraja.Keywords: Behavioral Counseling, Shaping Technique, Self Affiliation